Surface crack growth prediction under fatigue load using the S-version Finite Element Model (S-FEM) - M. N. M., Husnain; M. R. M., Akramin; Z. L., Chuan (IOP Publishing Ltd., 2019)
Prediction of fatigue crack growth is one of the vital issues to prevent catastrophic failure from damage tolerance perspective. The surface of crack shape usually in semi-elliptical that maintained during the whole propagation. The investigation of this paper is to illustrate the surface crack growth that subjected to fatigue loading. The four-point bending and three-point bending have been simulated by using the S-version Finite Element Model (S-FEM). The simulation is conducted for aluminium alloys A7075-T6 and A2017-T3 with all of the parameters based on the previous experiment. The semi-elliptical crack shape is applied during the simulation process to represent with the reality of crack growth phenomena. Paris’ Law model approach is presented in fatigue crack growth simulation. The S-FEM produced the surface crack growth and fatigue life prediction. The results of the S-FEM prediction then compared with the previous experiments. The results presented in a graph for comparison between S-FEM prediction with the experimental results. The S-FEM results obtained is good agreement with the experiment results.